STUDY OF IMPLEMENTATION OF RELIABILITY CENTERED MAINTENANCE (RCM) IN PLTU SURALAYA A STUDY CASE OF PULVERIZER, MPS-89N TYPE, 5-7 UNITS - (NIM : NIM : 23108327); Pembimbing : Prof. Dr. Ir. H. Indra Nurhadi, ZULFADHLI
PLTU Suralaya has 7 steam power plants with total power 3400 MW, has operated for more than 10 years, needs more effective and efficient maintenance system. Maintenance system that runs today tends to use preventive maintenance approach in which the handling of all failure modes in the interval is almost the same time, without fully utilizing the reliability of data analysis as the basis of maintenance. RCM (Reliability Centered Maintenance) was a concept that combines the strategy of maintenance reactive, preventive, predictive and proactive maintenance to maximize machine life. Reliability of data used for machine maintenance planning. In this study conducted a study of the application of RCM, especially in type MPS pulverizer machine-89N units 5-7 as the starting point of the increase in power plant maintenance system Suralaya. Reliability data of this pulverizer derive from inspection data, machine failure data and monitoring condition data. Analysis of reliability involves exponential, normal and 2-parameter Weibull probability distribution approaches according to basic failure mode of machine components. The result of analysis of reliability data is effective time interval to implement a maintaining action to pulverizer. This study produced the analysis of RCM spells out that the main function of pulverizer consists of 32 components, 80 functional failures and 151 failure modes. Propose tasks for handling each mode failure are 1 reactive maintenance task, 111 preventive maintenance tasks, 12 predictive maintenance tasks, 10 proactive maintenance tasks and 17 failure finding tasks. The propose task performance is equipped with time interval obtained from reliability analysis result and departments responsible for propose tasks i.e. machine maintenance, electrical maintenance, instrument control maintenance, and operator and engineering departments.